A two-site reactive platform in the synthesis of amino-functionalized amphiphilic molecules via sulfenic acids. Issue 37 (9th September 2022) - Bonaccorsi, Paola; Gangemi, Chiara Maria Antonietta; Greco, Valentina; Gattuso, Giuseppe; Barattucci, Anna
Abstract : The synthesis of some bolaamphiphiles is described. Abstract : The synthesis of some bolaamphiphiles is described. It is a convergent approach that allows the linkage of a glucosyl derivative to a bis-functionalized platform, via a copper-free Sonogashira cross-coupling. The central core was obtained from the reaction of a suitably substituted bis-sulfoxide with diethynyl benzenes. The intermediates of such reaction are sulfenyl functions that are easily added to one triple bond of the unsaturated molecules. The functionalization at the central core, through the nucleophilic addition of ammonia or piperidine onto the two vinyl sulfonyl groups already present in the backbones of the molecules, opened the way to the preparation of more complex derivatives. The observation of the formation of new stereogenic carbons with an unexpected significantly high diastereoselectivity was justified and supported by preliminary theoretical calculations. The two ending glucosyl moieties were favourably deprotected to afford the amino-functionalized bolaamphiphilic molecules.